A BIM and construction productivity study on precast concrete installation - Sun, Jing Xiang (2015)
The construction industry in Singapore has been making efforts to improve productivity. To achieve this goal, the government has stressed repeatedly the importance of Building Information Modelling (BIM) and precast technology as game changers. This paper studied the existing methods and challenges of precast concrete installation. Several practical methods were proposed to address these issues according to industrial experience. The results of the study showed that some challenging problems of precast concrete installation could be resolved using BIM technology.